Growth dynamics and yield of eggplant (Solanum melongena L.) modeled with logistic curves - Barraza-Alvarez, Fernando Vicente; Barraza-Monterrosa, Angel Vicente; Barraza-Monterrosa, Luz Angela (Revista de Ciencias Agrícolas, 2026)
Eggplant is a traditional horticultural crop in the Colombian Caribbean. A descriptive and quantitative study was conducted to characterize its growth dynamics, biomass accumulation, and yield. The study used the Early Long Purple genotype, planted at 1.50 m between rows and 80 cm between plants, and included 960 replications over an area of 1,152 m². The objective was to characterize and quantify growth variables, dry matter accumulation, and yield in order to describe growth dynamics and identify key stages for agronomic management of the crop. The variables evaluated from transplanting until 135 days later included: plant height, main stem diameter, number of leaves, leaf area, total dry matter per plant, and yield. The measurements obtained were fitted to a logistic model using the PROC NLIN procedure of SAS software (Statistical Analysis System). Descriptive statistics, including mean, standard deviation, coefficient of variation, maximum value, and minimum value, were obtained. Coefficients of determination greater than 90% were found, with sigmoidal growth patterns. The maximum values observed were: 68.33 ± 0.81 cm for plant height, 10.85 ± 0.49 mm for stem diameter, 79.27 ± 1.13 leaves per plant, 3,392.10 ± 0.78 cm² of leaf area, 46.68 ± 1.25 g of total dry matter per plant, and a yield of 63.64 ± 0.05 t·ha⁻¹. In conclusion, the greatest vegetative growth occurred between 30 and 60 days after transplanting (DAT). Therefore, this period represents an optimal window for implementing agronomic management practices aimed at maximizing dry matter accumulation and promoting balanced crop growth and development.